Jovens universitários e álcool: conhecimentos e atitudes. - Bresighello, Maria Luísa Moura (2005)
This quantitative-qualitative research was developed with the objectives to evaluate the alcohol consumption through the Alcohol Use Disorders Investigation Test - AUDIT, between the students of graduation of the course of Physics, of the Universidade Estadual Paulista - UNESP, Campus Rio Claro and, to identify to the knowledge and attitudes of these students on the alcoholic beverage ingestion. The results gotten in the initial stage of the research -quantitative - had allowed the aiming of the following stage - qualitative. Interviews half-structuralized with eight students of the 30 had been carried through that they had answered to Test AUDIT. The results of the related test had shown that, little more than 83% present standard of consumption of low risk. The transcription and analysis of the interviews had allowed a deepening in the universe of these students, where it was possible to apprehend part of its knowledge and attitudes with relation to the alcohol, and the identification of the factors of vulnerability and empowerment. The orientation necessity was clear, to the adults who coexist young and children, on the curses of the alcoholic beverage use and on the necessity of a bigger attention to those situations that come to facilitate its use. It was possible also to perceive the importance of the family as factor of support to the behavior of these young. How much to the pertaining to school environment, it was verified that it lacks to preparation to the educators and professionals of the health, and a bigger reflection on the part of all the society, so that the question of the alcoholic beverage consumption is faced as catalytic of sad future consequences for children and young. The educative work must exceed the field of the information and the university must dare and go beyond the knowledge technician, for the integral formation of the diverse professionals who for it pass.